#### Answer

a) 0
b) 9
c) 9

#### Work Step by Step

a) f(-1) = (-1)^{3} + 1 = -1 + 1 = 0
b) f(2) = 2^{3} + 1 = 8 + 1 = 9
c) f(2) - f(-1) = 9 - 0 = 9

Published by
Brooks Cole

ISBN 10:
1305071751

ISBN 13:
978-1-30507-175-9

a) 0
b) 9
c) 9

a) f(-1) = (-1)^{3} + 1 = -1 + 1 = 0
b) f(2) = 2^{3} + 1 = 8 + 1 = 9
c) f(2) - f(-1) = 9 - 0 = 9

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.